DIVERSITAS ODONATA DI KAWASAN EKOWISATA SUBAK SEMBUNG, DENPASAR UTARA - Ni Luh Putu Nadia Febryanti; Ni Made Suartini; Sang Ketut Sudirga (SIMBIOSIS, 2025)
The Odonata order comprises two suborders: dragonflies (Suborder Anisoptera) and damselflies (Suborder Zygoptera). This research aim to detect the species and level of diversity of Odonata present in the Subak Sembung Ecotourism Area, located in the northern region of Denpasar. The research was carried out in June until July 2024 using an exploratory method at three observation points in different Odonata habitats. Each habitat was explored in the morning from 08.00 to 11.00 WITA and in the afternoon from 15.00 to 17.00 WITA. Sampling was repeated three times. Odonata samples obtained from the three habitats were then identified through the observation of morphological characteristics. Enviromental factors were measured at each point and sampling, including altitude, air temperature and humidity. Based on the results of the research carried out six spesies of Odonata were found, namely Ischnura senegalensis, Agriocnemis femina, Agriocnemis pygmaea, Pseudagrion pruinosum, Orthetrum sabina and Crocothemis servillia. Odonata data from three different habitats were calculated by diversity index, which was categorized as moderate in the kale habitat with a value of 1,36, while the water henna habitat and rice habitat were categorized as low with values of 0,55 and 0,79. Keyword: Dragonflies, ecotourism, diversity, Odonata, Subak Sembung